Survival and associated predictors for patients with pineoblastoma or pineal parenchymal tumors of intermediate differentiation older than 3 years: Insights from the National Cancer Database. Issue 1 (17th April 2022) - Kerezoudis, Panagiotis; Yolcu, Yagiz Ugur; Laack, Nadia N; Ruff, Michael W; Khatua, Soumen; Daniels, David J; Burns, Terry C; Kizilbash, Sani H
Abstract: Background: The management of pineal parenchymal tumors remains controversial. Methods: The 2004-2017 National Cancer Database was queried for cases (age >3 years) with histologically confirmed pineal parenchymal tumors of intermediate differentiation (PPTID, n = 90) or pineoblastoma (n = 106). Results: Within the PPTID group, median age was 41 years; 49% were males. Five- and 10-year survival were 83% and 78%, respectively. Adjuvant radiation and chemotherapy were administered in 64% and 17% patients, respectively. The effect of radiation with or without chemotherapy (HR 1.15, P = .81, and HR 1.31, P = .72, respectively), and extent of resection (HR = 1.07, P = .93) was not significant. Within the pineoblastoma group, median age was 25 years; 51% were males. Five- and 10-year survival were 66% and 42%, respectively. Adjuvant radiation and chemotherapy were administered in 72% and 51%, respectively. In multivariable analysis, patients with pineoblastoma who received both radiation and chemotherapy (n = 39) had significantly lower hazard of death (HR 0.35, 95% CI 0.14-0.85, P = .02) compared to those who received radiation alone (n = 20) or no adjuvant treatment (n = 19). Finally, females in the pineoblastoma group were found to have a lower hazard of death compared to males (HR 0.24, 95% CI 0.10-0.58, P = .001); this comparison trended toward statistical significance in the PPTID subgroup (HR 0.40, 95% CI 0.14-1.08, P = .07). Conclusions: Survival rates were higher in patients with PPTID vs patients with pineoblastoma. Adjuvant chemoradiation was associated with improved survival in pineoblastoma and females had lower hazards of death. Further research should identify specific patient profiles and molecular subgroups more likely to benefit from multimodality therapy.